2001
DOI: 10.1086/322029
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Capsular Polysaccharides of Group BStreptococcusin Pregnant Canadian Women: Relationship to Colonization Status and Infection in the Neonate

Abstract: In a cohort study of 1207 pregnant women in Alberta, Canada, the serotype distributions of vaginal-rectal group B Streptococcus (GBS) isolates were compared with all isolates from neonates with invasive GBS disease identified by population-based surveillance. Serum concentrations of Ia, Ib, II, III, and V capsular polysaccharide (CPS)-specific IgG also were determined, according to serotype of the vaginal-rectal colonizing GBS strain. GBS colonization was detected in 19.5% (235 of 1207) of women. Serotype III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
68
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 45 publications
8
68
1
5
Order By: Relevance
“…Indeed, previous studies have reported that CPS type III GBS strains induce a lower maternal antibody response 34 and are more virulent. Since newborn infants rely on the transfer of maternal antibodies for defense against infections early in life, the low antibody response to type III strains could explain the high rate of type III infections.…”
Section: Cps Type Percent Survivalmentioning
confidence: 98%
“…Indeed, previous studies have reported that CPS type III GBS strains induce a lower maternal antibody response 34 and are more virulent. Since newborn infants rely on the transfer of maternal antibodies for defense against infections early in life, the low antibody response to type III strains could explain the high rate of type III infections.…”
Section: Cps Type Percent Survivalmentioning
confidence: 98%
“…Alternatively (though less desirably), surrogate immunological measures of clinical efficacy based on maternal and neonatal serotype-specific IgG antibody may be sufficient endpoints. 25,48 RECOMMENDATIONS What is the best preventive strategy for the UK? Table 7 summarizes estimates of the numbers of deaths and cases of serious disability estimated to be prevented by each of the three preventive strategies.…”
Section: Conducting a Trialmentioning
confidence: 99%
“…Maternal GBS colonization is a main risk factor for neonatal disease, and roughly 20 to 40% of pregnant women are colonized (14,23). Colonization rates of up to 31% and 34% have been documented in young men (4) and nonpregnant women (4,42), respectively, whereas a rate of 22% has been observed in individuals over 65 years of age (18).…”
mentioning
confidence: 99%